(untitled) - ROBERTSON, HOWARD (Gran Bretaña, 1960)
1.List of illustrations / 2.Programme organisation plan / 3.The structure / 4.Materials for the exterior / 5.Expression / 6.External details / 7.Interior decoration / 8.The house / 9.The modern movemente and architectural education
Incluye indice analitica pag.225
Keywords: ARQUITECURA